(3Yde GdELJeGY GdeYQaj s - (3Ced MSf (B, (3CMeOs ((3YeGf(B:s (3OGQ GdeSjQI ddfTQ hGdJhRjY (B,s, 2015)
(3jVe eSCdI GdeYQaI GdeGgjI heQGMd GdJWhQ GdeYQaj, GdeYQaI Hjf GdadSaI hYde GdELJeGY heQGMd GdJWhQ GdeYQaj, fTCI Yde GdELJeGY Hjf GdacQ hGdhGbY, Yde GdELJeGY GdeYQaj hGdQDi GdfXQjI hCge GdbVGjG GdeYQajI, GdeKba GdeYGUQ hJMOjGJ GdYhdeI, GdeKba GdYQHj hGdghjI hGdOhQ aj VhA GdhGbY GdKbGaj GdeMdj hGdYGdej, hjVe Cge GdOQGSGJ GdeYGUQI aj Yde GdELJeGY GdeYQaj, GdKbGaI GdEdcJQhfjI aj Xd eLJeY GdeYQaI JMdjd ShSjhdhLj Mhd CSJNOGe GdTHGH dTHcI GdEfJQfJ hGdeOhfGJ, JMdjd dOQGSI GdfU hGdSdWI hGdeLJeY hGdbje GdSjGSI aj GdQhGjI GdYQHjI(B. s
(3HHdjhZQGajG(B: (3U(B.459-472s
Keywords: (3GdELJeGY GdeYQaj, Ydes; (3GdYdhe GdELJeGYjIs